Case Report: Severe Hypercalcemia Following Vitamin D Intoxication in an Infant, the Underestimated Danger of Dietary Supplements - Gérard, Alexandre O.; Fresse, Audrey; Gast, Myriam; Merino, Diane; Gourdan, Pierre; Laurain, Audrey; Margaritis, Irène; Gauci, Pierre-Alexis; Huret, Fanny; Parassol, Nadège; Rocher, Fanny (Frontiers in Pediatrics, 2022)
Vitamin D supplementation is routinely introduced in infants, according to medical guidelines. However, vitamin D overdose can result in life-threatening hypercalcemia. We report the case of a 3-month-old infant who suffered from severe hypercalcemia. Upon detailed questioning of the parents, a vitamin D administration error has been identified. Indeed, the parents had followed the advice of their midwife. They substituted the prescribed medicinal vitamin D by a dietary supplement, different in concentration and dosing, without performing the dose conversion needed. In fact, many different medications and dietary supplements with vitamin D exist, offering various concentrations and units of measurement. This case highlights the pivotal role of therapeutic education. Broadly, there is a need for harmonization of the regulation and labeling of dietary supplements and medications containing vitamin D.